Spatial Analysis of 5-Star Hotels in Istanbul - Kutlu Demirer (European Regional Science Association (ERSA), 2011)
Turkey has achieved great success in the tourism sector which started a greater than ever trend towards hotel investments. While, new investors are entering to the market, international brands are pursuing strategies to increase their existing supply. Istanbul, Turkey's largest city, besides being a world-famous tourist attraction, also draws substantial foreign investment which escalates both the demand and supply in the hotel market. In the light of previous researches conducted by Dökmeci and Balta (1999) this research focuses on the supply side and the spatial development of high-end hotels in Istanbul. By revisiting the works of von Thünen and Alonso, compares rings of urban location for hotels in Istanbul in terms of rent as overnight room rates. Location data are accumulated from Ministry of Tourism, local municipalities, chambers and unions. Overnight hotel rates were collected through internet booking sites, telephone inquiries and visits during October, November and December of 2010. As the polycentric development of the city has increased over the last decade and many functions have been decentralized or shifted, the analysis reveals valuable insight into urban tourism pattern. The results coincide with the concentric rings described by the previous researches although many new hotels were constructed, new sub-centers had formed and the importance of sub-centers has increased dramatically.
Keywords: 330